2012
DOI: 10.1519/jsc.0b013e31822602fa
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Intensity on Rating of Perceived Exertion During a Multiple-Set Resistance Exercise Session

Abstract: The aim of this study was to analyze the effects of intensity on rating of perceived exertion (RPE) during a multiple-set resistance exercise session. Fourteen men (22.9 ± 3.8 years) with previous experience in resistance training (22.9 ± 3.8 years) performed 2 experimental sessions in random order: resistance exercise at 50% of 1 repetition maximum (1RM) (E50%) and resistance exercise at 70% of 1RM (E70%). In both sessions, 5 exercises (bench press, bent-over row, frontal raises, arm curl, and overhead tricep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 22 publications
2
22
0
1
Order By: Relevance
“…All exercises were performed using free weights or universal weight machines. The maximum strength for every exercise was measured using the 1RM method 41 .…”
Section: Methodsmentioning
confidence: 99%
“…All exercises were performed using free weights or universal weight machines. The maximum strength for every exercise was measured using the 1RM method 41 .…”
Section: Methodsmentioning
confidence: 99%
“…(30). A rating of 0 was associated with no effort (seating or resting), and a rating of 1 corresponded to the perception of effort while performing an extremely easy effort (26). A rating of 10 was considered to be maximal effort and associated with the most stressful exercise ever performed (23).…”
Section: Control Of the Rating Of Perceived Exertion (Rpe)mentioning
confidence: 99%
“…Numerous studies have revealed that participants report increasingly higher RPE values with increasing load/torque demands [3][4][5][6][7][8] even when matched for volume-load (repetitions x load) [9][10][11] . In addition a number of studies have reported a relationship between load, RPE and physiological measures such as: electromyography amplitude 3,6,8,12 , heart rate 5 , and blood lactate 12,13 .…”
Section: Introductionmentioning
confidence: 99%